스프링클러 설비의 동배관 부식 개선에 관한 연구 - 문철환(Chul-Hwan Mun); 최유정(Yu-Jung Choi); 최재욱(Jae-Wook Choi) (한국화재소방학회 논문지, 35(2), 2021)
소방용 수계시스템에 적용되고 있는 동(Copper)배관은 철(Steel)에 비해서 상대적으로 내식성이 우수한 제품으로2010년도를 전후로 공동주택에 많이 적용하였으나, 공식(Pitting)에 따른 배관 누수로 인해 소방의 성능이 확보되지못하고 있다. 이러한 문제점을 해결하기 위하여 배관을 다른 재질(STS, C-PVC 등)로 교체 할 경우 관계자들의 경제적 손실과 입주자들의 불편함이 확대될 수밖에 없는 실정이다. 2018년 E지역에서 27건의 누수가 발생하였으나 부식억제제를 투입한 결과 1건으로 감소하는 것을 확인하였다. 따라서 2020년 10월부터 2개월 동안 전국 5개 지역 2,000여 세대에 대하여 2차 배관 부식 개선 연구를 통해 A 지역 5개 동의 정체된 소화수(수돗물)에서 pH 8.34~9.08, ORP-94.9~-135.8 mV, EC 0.097~0.137 ms/cm의 범위 값이 도출되어 개선이 필요함을 확인하였다. 부식억제제를 주입한결과 pH 11.13 ~ 11.26, ORP -257~-265.5 mV, EC 4.189~5.769 ms/cm로 나타났다. 수용성규산염은 양극부분의 금속배관 표면에 흡착되어 얇은 단분자막을 형성하여, pH를 증가시켜 알칼리화를 유도하고 ORP를 낮추어 환원성을 높임으로써 부식방지에 효과가 있는 것으로 판단된다. Copper pipes used in fire sprinkler systems are somewhat superior to steel pipes in terms of corrosion resistance. Theyhave been widely used in apartments since 2010, but their firefighting performance has not been firmly established due toleakage caused by pitting. In order to solve this problem, copper pipes need to be replaced by pipes made of other materialssuch as STS or C-PVC, which, however, would impose an economic burden on the party responsible for maintenance, aswell as economic loss to other relevant parties and inconvenience to residents. Although 27 leakages occurred in the Eregion in 2018, it was found that the number of incidents was reduced to just one case after an application of corrosioninhibitor. Therefore, for 2 months beginning in October 2020, a second project to reduce piping corrosion was conductedwith 2,000 households in five regions nationwide. During this period, the standing fire water of five apartment buildingsin the A region was measured as having a pH 8.34–9.08, an ORP -94.9–-135.8 mV, and an EC 0.097–0.137 ms/cm, whichindicated a need for improvement. Subsequently, a corrosion inhibitor was poured into the fire water, resulting in improvedvalues of pH 11.13–11.26, ORP -257–-265.5 mV, and EC 4.189–5.769 ms/cm, which demonstrated the effect of preventingpipe corrosion. It was evident that water-soluble silicate was adsorbed on the metal pipe of the anode to form a thinmonolayer, which induced basicity by increasing the pH and by decreasing the ORP, which eventually minimized corrosion. KCI Citation Count: 0